2022
DOI: 10.3389/fnbeh.2022.848232
|View full text |Cite
|
Sign up to set email alerts
|

S-Ketamine Pretreatment Alleviates Anxiety-Like Behaviors and Mechanical Allodynia and Blocks the Pro-inflammatory Response in Striatum and Periaqueductal Gray From a Post-traumatic Stress Disorder Model

Abstract: This study aims to explore the regulatory effect of S-ketamine on the mechanical allodynia, anxiety-like behaviors and microglia activation in adult male rats exposed to an animal model of post-traumatic stress disorder (PTSD). The rat PTSD model was established by the exposure to single-prolonged stress (SPS), and 1 day later, rats were intraperitoneally injected with 5 mg/kg S-ketamine or normal saline, respectively. Paw withdrawal mechanical threshold was measured 2 days before, and 1, 3, 5, 7, 10, 14, 21 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In fact, esketamine has shown antidepressant effects in preclinical research [ 8 , 9 ] and clinical trials [ 10 , 11 ], which may have had significant implications in reducing the risk of relapse to cocaine in rats in the present study. Additionally, a very recent paper by Yang et al (2022) demonstrated that esketamine alleviated anxiety-like behaviours in a rat model of post-traumatic stress disorder [ 12 ]. Similarly, in male rats submitted to a panicogenic challenge, esketamine caused the rapid-onset of anxiolytic-like effects [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, esketamine has shown antidepressant effects in preclinical research [ 8 , 9 ] and clinical trials [ 10 , 11 ], which may have had significant implications in reducing the risk of relapse to cocaine in rats in the present study. Additionally, a very recent paper by Yang et al (2022) demonstrated that esketamine alleviated anxiety-like behaviours in a rat model of post-traumatic stress disorder [ 12 ]. Similarly, in male rats submitted to a panicogenic challenge, esketamine caused the rapid-onset of anxiolytic-like effects [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these observations, an intranasal delivery of esketamine (branded as Spravato ® ) was recently approved in the United States and Europe to treat treatment-resistant depression. Other findings indicate anxiolytic-like effects of esketamine [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both the open field test and tail suspension test have long been used to determine animals’ anxiety- and depression-like behaviors, respectively, in rodents ( Seibenhener and Wooten, 2015 ; Ueno et al, 2022 ). Specifically, the open field test has been widely used to measure the ketamine effects on anxiety-like behavior in rodents ( Guarraci et al, 2018 ; Pitsikas et al, 2019 ; Shin et al, 2019 ; Akillioglu and Karadepe, 2021 ; Yang et al, 2022 ; Acevedo et al, 2023 ). We thus measured locomotor activity and anxiety-like behavior using the open field test as carried out previously ( Shou et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Ketamine inhibited the LPS-induced increases in TNF-α, IL-1β, and nitrite in primary cultured microglia in a dose-dependent manner, which may be the result of inhibition of ERK1/2 phosphorylation [ 97 ]. In a rat model of post-traumatic stress disorder, esketamine reduced pro-inflammatory cytokines, NF-κB phosphorylation, and microglial activation in the dorsal striatum and periaqueductal gray [ 98 ]. In contrast to the above findings, ketamine also has pro-inflammatory effects.…”
Section: Mechanisms Underlying Gaa-microglia Interactionsmentioning
confidence: 99%